GERMANS IN AZERBAIJAN: RETROSPECTIVE ANALYSIS - ZEYNALOVA, Sudaba (CENTRAL ASIA AND THE CAUCASUS, 2005)
Azerbaijan, which is located between the West and East, became the home of representatives of many different nationalities at certain times throughout history. This ethnic diversity, which is still retained today, and the peaceful coexistence in our state of members of different nationalities, cultures, and confessions show the tolerance and respect the Azeris have for these people. Germans are also some of the representatives of the European culture who have lived for a long time in Azerbaijan. Looking at their lives and vital activity in this country is of special interest and presents a graphic example of the interrelationship between western and eastern cultures within a single society. Germans began migrating to Azerbaijan in the first decades of the 19th century for a number of reasons.1 The primary reason was the disastrous political and economic situation in Germany at this time as a consequence of the Napoleonic wars, which gave rise to mounting discontent among the masses and intensified the migration processes. The south of Germany, Württemberg, where dissident movements, including separatism, were becoming active, found itself in particularly dire straits. In search of salvation, some of its residents expressed the desire to move to the East, in particular to the Caucasus, since, in their opinion, it was located “not far from the cradle of the human race.”2 They made this request of Russian Emperor Alexander I, who, on his way back from the Vienna Congress in 1816, was traveling through Stuttgart.